مارسيل بيرتون وسياسيته في تونس والجزائر - سامية مرفوعة; د/عطية محمد (جامعة عمار ثليجي الاغواط, 2024)
ملخص : 91 ملخص ناللغة العربية: تبين الحقائق والمعلومات التي أوردناها في الفصهول أن المقهيم مرسهيل بيرتهون خهلال فتهرة حكمهه فهي الج ا زئهر وتهونس عمهل وناضهل مهن أجهل تطبيهق سياسهته بحيهث يمهس جوانهب مختلفهة منهها إداريهة واقتصهادية واجتماعيهة وههذه السياسهات جمعيهها تههدف إلهى فهر ويمنهة الاسهتعمار الفرنسهي فهي فتهرة تعهد مهن اههم الفته ا رت الاسهتعمار الفرنسهي لكهل مهن تهونس والج ا زئهر وذلهك خهلال الحرب العالمية الثانية. الكلمات المفتاحية: مرسيل بيرتون، السياسة ، تونس ، الج ا زئر. Summary in Arabic: . The facts and information that we mentioned in the chapters show that resident Marcel Berton, during his period of rule in Algeria, worked diligently in order to implement his policy in a way that affected various aspects, including administrative, economic, and social. All of these policies aimed to impose the dominance of French colonialism in a period that was considered one of the most important periods of French colonialism for everyone. Recommendation and Algeria during World War II. Keywords: Marcel Burton, politics, communication, Algeria.